2017
DOI: 10.1109/jmems.2017.2723626
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study of a Piezoelectric Vibration Energy Harvester Under High Temperature

Abstract: Abstract-This work focuses on studying the effect of increasing the ambient temperature up to 160• C on the power harvested by a MEMS piezoelectric micro-cantilever manufactured using an aluminum nitride-on-silicon fabrication process. An experimental study shows that the peak output power decreases by 60% to 70% depending on the input acceleration. A theoretical study establishes the relationship of all important parameters with temperature and includes them into a temperature-dependant model. This model show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…The harvester used in this work was made of piezoelectric aluminum nitride on a flexible substrate of polyimide (commercial Kapton). Theoretical models showed that harvester efficiency could experience a drop with temperature due to thermal stresses [35]. Noteworthy, no creeps in the aluminum nitride piezoelectric layer were observed with temperature, suggesting the harvesting device could withstand the temperature range measured.…”
Section: Piezoelectric Conversion From the Exhaust Pipe Under Real Driving Conditionsmentioning
confidence: 95%
See 1 more Smart Citation
“…The harvester used in this work was made of piezoelectric aluminum nitride on a flexible substrate of polyimide (commercial Kapton). Theoretical models showed that harvester efficiency could experience a drop with temperature due to thermal stresses [35]. Noteworthy, no creeps in the aluminum nitride piezoelectric layer were observed with temperature, suggesting the harvesting device could withstand the temperature range measured.…”
Section: Piezoelectric Conversion From the Exhaust Pipe Under Real Driving Conditionsmentioning
confidence: 95%
“…The calculation of the average gas speed starting from the measured mass flow rate has been performed using Equation (8). As described in previous work [34,35], the main component of the gas exhaust as it is in the air is N 2 . When considering the gas properties, neglecting the combustion products the error is typically not higher than 2%, therefore we have used air density when needed for the gas exhaust.…”
Section: Validation Of Gas Speed Measured By Pitot Tubementioning
confidence: 99%
“…Temperature variations in the actual service environment can affect the performance of the probe. Previous studies have demonstrated that temperature variations affect the performance of piezoelectric devices, triggering phenomena such as impedance value change [59], peak frequency shift [60], and even loss of operational performance. Therefore, it is necessary for the proposed corrosion probes based on EMI technology to consider the effect of temperature variation in the actual service environment.…”
Section: Temperature Sensitivity Analysismentioning
confidence: 99%
“…VEH technologies include a variety of transducers and scales, including macroscopic or mesoscale electromagnetic [8,9,10,11] and piezoelectric [12,13,14,15] generators to MEMS-scale electrostatic [16] and piezoelectric [17,18,19] harvesters. Research efforts in the VEH field include attempts to increase the operational bandwidth [20,21], operate at low frequency [22] or high temperature [23], improved electronic power conditioning efficiency [24,25] or mechanical efficiency [26,27]. In relation to the integration with composite materials, piezoelectric films are particularly suitable due to the thin profile and manufacturing compatibility [28,29].…”
Section: Introductionmentioning
confidence: 99%